Control System for BLDC (Brushless Direct Current) Motor in Electric Vehicles - Adam, Adam; Abidin, Zainal; Efendi, Zulfan; Alkhalefi, Dhani; Budiman, Ismail; Prasetyo, Bagas (ABEC Indonesia, 2024)
Electric vehicles represent an effective alternative to reduce environmental pollution caused by emissionsfrom fossil fuel-powered vehicles. This study utilizes a 1500-watt Brushless Direct Current (BLDC) motor as the drivemotor. Unlike conventional DC motors, BLDC motors operate with three phases, requiring an automation system toensure optimal distribution of current and voltage across each phase. For motor control, a Convenient Speed Controlsystem with a maximum power of 3000 watts is implemented. This system allows the vehicle to move forward andbackward, as well as enabling manual throttle operation. During the experiment, the fully charged battery displayed aninitial voltage of 53.2 volts for the forward mode and 52.8 volts for the reverse mode. The current required for forwardmovement was measured at 18 A, while for reverse it was 12.9 A. The minimum speed achieved by the electric vehiclewas 88.8 RPM, whereas the maximum recorded speed was 316.9 RPM. Thus, this control system is not only efficient inregulating speed but also provides flexibility in operating the electric vehicle, supporting efforts toward moreenvironmentally friendly transportation solutions.